1996
DOI: 10.1557/jmr.1996.0023
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of barium titanate thin films

Abstract: Polycrystalline films of barium titanate (BaTiO 3 ) have been synthesized on titanium (Ti) substrates by the galvanostatic anodization of Ti in a solution of 0.4 M Ba(OH) 2 . Crystalline films are formed at temperatures under 100 ± C within 10 min at a current density of 25 mA͞cm 2 at atmospheric pressure. Crystallinity of the films is found to increase with both current density and time of reaction. At 90 ± C, a film of 1 mm thickness is formed after 10 min; grain sizes up to 0.5 mm are obtained. Microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…31-174. The formation of the cubic BaTiO 3 phase, observed in this work, is quite common in the hydrothermal treatment of titanium-loaded precursors in Ba(OH) 2 solution. Figure a shows an XRD pattern of a PPS film, and Figure b shows the typical XRD pattern of a titanium oxide film. It is confirmed that the sol−gel titanium oxide film is XRD-amorphous.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…31-174. The formation of the cubic BaTiO 3 phase, observed in this work, is quite common in the hydrothermal treatment of titanium-loaded precursors in Ba(OH) 2 solution. Figure a shows an XRD pattern of a PPS film, and Figure b shows the typical XRD pattern of a titanium oxide film. It is confirmed that the sol−gel titanium oxide film is XRD-amorphous.…”
Section: Resultssupporting
confidence: 52%
“…The CO 2 might be introduced with starting solution, the thermal decomposition of organic components available in the sol−gel-derived film, and the PPS polymer substrate under hydrothermal conditions. It was reported that such BaCO 3 contamination could be avoided by washing with CO 2 -free, ammoniated water at pH 9, but we found that the kind of washing could not completely remove the BaCO 3 contamination on the top of the BaTiO 3 grains. Incubated in pH 9, CO 2 -free water under N 2 atmosphere for 10 min, then washed thoroughly with CO 2 -free water, rinsed in ethanol, and dried under N 2 atmosphere, the BaCO 3 contamination could be extensively removed.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…BT thin films have been prepared by a variety of deposition techniques, such as evaporation (thermal, flash and two-boat), sputtering (r.f. and magnetron), ion beam deposition, pulsed laser ablation deposition (PLD), electrochemical synthesis, 18 metal-organic chemical vapor deposition (MOCVD) 19 and others. 20 -22 Recently, significant attention has been given to the synthesis of BT thin films by the sol-gel or modified sol-gel technique.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38] The currently obtained results obviously benefit from the soluble property of the potassium carbonate. It is worth mentioning that for some dielectric films prepared by the hydrothermal or hydrothermalelectrochemical method, such as BaTiO 3 films, BaCO 3 always contaminates the formation of the BaTiO 3 films, although such surface contamination could be avoided by careful washing with CO 2 -free ammoniated water at pH 9.…”
Section: A Structural Characterizationmentioning
confidence: 99%